2022
DOI: 10.6018/red.499171
|View full text |Cite
|
Sign up to set email alerts
|

Factores determinantes que permiten establecer tipologías de profesorado en el contexto de la innovación tecnológica educativa.

Abstract: The figure of the teacher plays a fundamental role in the integration of digital technologies (TD) in the teaching-learning process. From this perspective, several studies have been carried out with the aim of defining the most influential variables and/or factors in the adoption, use and integration of TD from the teacher's perspective, of which very few conclude with a clear definition. From this point of view, the study aims to design an explanatory theoretical instructional model of the different teacher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…One of the limitations of the study is the focus only on teachers; we believe that further studies should be extended to students and university administrative staff. Students are essential educational actors in the digital transformation; although studies recognize that "the success of the technology-mediated educational process depends, to a large extent, on the adoption and use of digital technology by faculty" [6] (p. 1), other studies have found that successful ICT implementation requires student engagement [30].…”
Section: Limitations and Prospects Of The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…One of the limitations of the study is the focus only on teachers; we believe that further studies should be extended to students and university administrative staff. Students are essential educational actors in the digital transformation; although studies recognize that "the success of the technology-mediated educational process depends, to a large extent, on the adoption and use of digital technology by faculty" [6] (p. 1), other studies have found that successful ICT implementation requires student engagement [30].…”
Section: Limitations and Prospects Of The Studymentioning
confidence: 99%
“…Digital transformation is understood as the process of disruption and change where organizations use strategic responses to create value [5] (p. 118). This digital transformation is related to multiple actors, with the teacher as one of the central actors, because as explained by [6] "the figure of the teacher plays a key role in the integration of digital technologies in the teaching-learning process" (p. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, el estudio acredita que existe una asociación entre la formación digital recibida antes de la pandemia y el nivel de competencia digital auto percibido. En este sentido, investigaciones previas han subrayado que la necesidad percibida de formación en tecnologías digitales (Gil-Flores et al, 2017), así como las actitudes y las creencias de los docentes con respecto a la tecnología, son factores que influyen de manera significativa en la integración y uso de las tecnologías (Cartagena Beteta et al, 2022;Hidalgo-Cajo & Gisbert-Cervera, 2022). Esta investigación ha inferido a partir de las variables consideradas cinco perfiles digitales: objetores, en el que estarían representados aquellos docentes carentes de competencia digital o con un bajo dominio de esta, y que no identifican la utilidad de las tecnologías digitales en su práctica docente (Sosa & Valverde, 2020).…”
Section: Discusión Y Conclusionesunclassified
“…Sin duda los resultado obtenidos permiten conocer desde el modelo TAM las percepciones de los actores educativos que en la mayoría de los análisis tienden a ser positivos en el profesorado en la aceptación y uso de la tecnología, sin embargo en el estudiantado no lo perciben totalmente así, ya que la dimensión de disfrute no contribuye en la aceptación y uso de MOODLE por parte de este grupo analizado, esta situación posiblemente se presenta por el cambio de modalidad de estudios que se aplicó de manera abrupta y rápida, con el desafío del profesorado de enseñar a nativos digitales; y que si bien el profesorado utilizo una herramienta efectiva eficiente y eficaz para el desarrollo del proceso educativo, para el estudiantado no lo percibe de la misma manera, desde este punto de inflexión cabe señalar que muchos estudios demuestran que el aprendizaje virtual está por debajo de la expectativa utopista, debido a que el profesorado no se encuentran lo suficientemente formados y capacitados en sinergia con las habilidades tecnológicas y pedagógicas necesarias (Hidalgo-Cajo y Gisbert-Cervera, 2022), que permitan a los estudiantes engancharse en un entorno virtual compuesto por actividades y recursos dinámicos, entretenidos, colaborativos y cooperativos que provoquen en ellos la satisfacción de disfrute percibido al usar MOODLE.…”
Section: Discusión Y Conclusionesunclassified